Interdisciplinary Competences and Their Status Role in the System of Higher Professional Education - Kachalov N. A. Nikolay Aleksandrovich; Kornienko A. A. Alla Alexandrovna; Kvesko R. B. Raisa Bronislavovna; Kornienko A. A. Anna Anatolievna; Kvesko S. Svetlana; Chaplinskaya Ya. I. Yana Igorevna (2015, 2015)
Title screen